Advance Heat Tolerant Potato Hybrids Performance for Yield and Quality Parameters under Hot Prone Area - Sadawarti, Murlidhar; Gupta, V. K.; Samadhiya, R. K.; Singh, S. P.; Singh, R. K.; Katare, Subhash; Roy, Satyajit; Chakrabarti, S. K.; Verma, Dharminder (International Journal of Bio-resource and Stress Management, 2022)
Field trial was conducted under AICRP (Potato) at ICAR-CPRI, Regional station, Gwalior, Madhya Pradesh, India during 2017−18, 2018−19 and 2019−20 with advanced potato hybrids viz. HT/7-1105, HT/7-620 and HT/7-1329 along with controls Kufri Lima, Kufri Surya, Kufri Khyati and Kufri Lauvkar in RBD with 3 replications during second week of October every year. Emergence among hybrids and varieties was >85.0%. Plant vigor was higher in Kufri Lima (4.4) followed by HT/7-1329 and Kufri Surya (4.0). At 60 days, all the hybrids except HT/7-620 recorded significantly higher tuber dry matter over Kufri Khyati (15.0%). At 75 and 90 days, 2 hybrids and controls except Kufri Khyati recorded significantly higher dry matter over hybrid HT/7-620 (17.4% for 75 days and 18.1% for 90 days). Total tuber yield of Kufri Lima (23.5 t ha-1) followed by hybrid HT/7-1329 (23.4 t ha-1) at 60 days at same level of GDD (Growing degree days) of 1134, Kufri Lima (32.4 t ha-1) followed by Kufri Khyati (30.2 t ha-1) and hybrid HT/7-1329 (29.4 t ha-1) at 75 days at same level of GDD (Growing degree days) of 1291 and Kufri Lima (36.6 t ha-1) followed by hybrid HT/7-1329 (35.6 t ha-1) at 90 days at same level of GDD (Growing degree days) of 1426 recorded significantly higher or at par total tuber yield respectively than other controls/hybrids. Hybrid HT/7-1329 and Kufri Lima at 60, 75 and 90 days recorded highest economic return over other hybrids and varieties. Hence, Hybrid HT/7-1329 and variety Kufri Lima found to be most suitable for cultivation under early planting of hot prone areas of West-Central India for getting highest remunerative prices.